Problems and Obstacles of Cosmetic Marketing Business in Thailand - Atipongvanich, Chetsada (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
The purposes of this research are 1) to study factors affecting the marketing of cosmetics business in Thailand, 2) to study the environment, problems, and obstacles of the marketing of the cosmetics business and 3) to study guidelines in order to obtain higher efficiency of marketing operations in the cosmetics business. A sample group used in the research was 400 people of women and men aged 21-30 years who have bought cosmetics in the past 6 months and lived in Thailand. They were selected by convenience sampling. The tool used to collect data is a questionnaire created by the researcher. The content validity was between 0.67-1.00 and the reliability of the questionnaire was between 0.76-0.92. The data were analyzed using percentage, average, standard deviation, one-way Analysis of Variance, LSD pair testing and LSD analysis and multiple regression analysis with the Enter Method. The results were summarized in each aspect as follows. The research results revealed as follows: 1. In terms of factors affecting the marketing of cosmetics business in Thailand, differences in age, occupation and monthly income did not affect the marketing operation in the cosmetics business. 2. In the aspect of the environment, problems, obstacles of the marketing of cosmetics business in Thailand, there were limitations in online sales and system of data distribution pattern. Also the reliability in advertising products that could access the consumers in each group was limited. Market competitors provided plenty of choices for customers. After-sales service was not good and the manufacturers were also not ready, including the uses of low quality raw materials for the production. Customer brand stickiness made them not open-minded for importing of smuggled goods, trading fake or too-expensive-for-quality items and the use contaminants. Advertising and public relations did not create memory for users. The manufacturer did not comply with currently strict laws or controls. 3. For the study of guidelines for higher efficiency of marketing in cosmetics business in Thailand, operators in the cosmetics business should help each other to report whereabouts of unqualified production and create novelty in the product in order to respond to the needs of the market and analyze the goals of customers. Cosmetics product information should be presented to customers through various media that is currently seen and disseminated in all accessible media. Article history: Received 3 November 2019 Revised 21 December 2019 Accepted 24 December 2019 SIMILARITY INDEX = 0.00 %